Fine resolution basin database using 10m DEM at the area along Sanriku coast of Japan - Yamakita, Takehisa; Imaki, Hiroo (JAMSTEC REPORT OF RESEARCH AND DEVELOPMENT, 2019)
This fine resolution basin database provides basin model over 10ha sub-basins of the Sanriku coastal area located in the north west Pacific side of Japan. The data contain watershed boundary and flow path data about the target area created by use of a 10m digital elevation model (DEM). Using this data, the coverage area was increased over 721.66km2 compared to the low resolution public data set provided by the government. It increased the coastline coverage from 17% to 84% compared with the low resolution data set in 1km grid. For use in the coastal area or river discharge model, this data also contains the overall drainage basin boundary at the river mouth. The area of this survey was highly damaged by the tsunami on The 2011 Great East Japan Earthquake and post-disaster anthropogenic impact. Thus, this database will be of interest in the context of changes in land use and river discharge to assess both post-disaster anthropogenic impacts on the ecosystems.　Complete dataset is available via site:http://www.godac.jamstec.go.jp/catalog/data_catalog/metadataDisp/JAMSTEC-R_28DP01?lang=en&view=simple